Métodos de estimativa de descarga sólida em rios: análise comparativa - Brune, Rafaeli Alves (2014)
Sediment transportin watersheds is related to geomorphology, river ecology, engineering structures stability and navigation conditions, among many important water resources planning and control aspects. The large number of variables involved in the mechanics of sediment transport and the existing complexity in the interactions of physical processes make it difficult to establish precise indirect methodologies for estimating sediment transport in rivers. Hence, there is still no universally accepted indirect methodology. The main objective of this work is the comparative analysis of different empirical methods available in the literature for estimating solid transportin rivers, considering their specific characteristics and results of applications to the river Santa Joana and Santa Maria do Doce, Sossego e Santa Júlia watersheds, located in the lower portion of the Doce river basin, in Espírito Santo State, Brazil. Einstein Modified by Colby and Hembree (1955); Simplified Colby (1957); Engelund & Hansen (1967); Ackers & White (1973); Yang (1973), Karim (1998) and Cheng (2002) methods for indirect estimation of solid transport were applied. Considering the average estimates of discharge of solid bed material (Qsml) for campaigns developed during rainy periods for the Doce River cross section, the method of Karim (1998), followed by the method of Ackers & White (1973), showed the highest value, while the method of Yang (1973) showed the lowest. For Santa Joana and Santa Maria do Doce rivers and Sossego and Santa Júlia creeks, it was found that the Ackers & White (1973) method, followed by Karim (1998) and Yang (1973) methods, presented the highest values, while Cheng (2002) and Engelund & Hansen (1967) methods showed the lowest. The Simplified Colby method showed the highest estimates of total solid discharges (Qst) for all cross sections of all watercourses sampled. It was concluded that the application of the different indirect methods can result in large differences in estimates of sediment transportin river sand, thus, results from application of these methods should be taken with caution. The results showed the great importance of carrying out sediment transport measurement campaigns to assess sediment transport and choose the best indirect estimation methods for specific watercourses.